Managing Post-Disaster Reconstruction Finance : International Experience in Public Financial Management - Fengler, Wolfgang (World Bank, Washington, DC, 2012)
In recent years, natural and man-made disasters have confronted the international community with its most demanding reconstruction challenges since the aftermath of World War II. Managing the inflow of resources and spending those resources well have proven to be two of the main difficulties in such reconstruction projects, particularly after large-scale disasters. A central dilemma of the public financial management of reconstruction is the need for very high levels of accountability to demonstrate fiduciary credibility, while at the same time ensuring the rapid implementation of recovery programs. This paper identifies options and lessons for managing post-disaster reconstruction finance in three key areas: (i) the establishment of special institutions to manage the reconstruction process; (ii) the selection of public financial management systems with respect to the application of country systems, special fiduciary arrangements, or donor/NGO execution; and (iii) monitoring and evaluation systems. The authors synthesize the phasing of assistance and approaches in eight recent post-natural disaster reconstruction efforts (Aceh-Indonesia, Yogyakarta-Indonesia, Sri Lanka, Maldives, Pakistan, Colombia, Grenada, and Honduras) to help guide the priorities and options for future instances of public financial management for disaster reconstruction. The paper also compares the challenges posed by post-conflict versus post-natural disaster public financial management.